Negative electrode sheet and battery containing the same

By adjusting the particle size ratio of SBR and negative electrode active substances, the structure of the negative electrode sheet in lithium-ion batteries is optimized, which solves the problems of lithium ion conduction difficulties and the serious lithium evolution at low temperatures, and improves the dynamic performance of the battery.

CN116190566BActive Publication Date: 2025-02-28CALB GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310470011.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-02-28
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, when SBR is used as the negative electrode binder, it leads to difficulty in conduction of lithium ions during charging and discharging. Especially under low temperature conditions, lithium-ion excision of the negative electrode is severe, affecting the dynamic performance of the battery.

Method used

By adjusting the particle size ratio of SBR and negative electrode active substances in the negative electrode active coating, ensuring 6≤D1/D2≤100, optimizing the relative size of SBR and negative electrode active substances, enhancing adhesion and retaining active sites, and improving lithium ion transport efficiency.

Benefits of technology

The transmission efficiency of lithium ions in the negative electrode sheet is improved, especially under low temperature conditions, the dynamic performance of the battery is optimized, and the electronic impedance and ion impedance of the negative electrode sheet are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a negative electrode sheet and a battery containing the same. The negative electrode sheet includes a negative electrode active coating, the negative electrode active coating includes a negative electrode active material and a negative electrode binder, and the negative electrode binder includes SBR; the particle size D1 of the negative electrode active material and the particle size D2 of the SBR satisfy 6≤D1 / D2≤100. In the negative electrode sheet provided by the present invention, the relative size of SBR and the negative electrode active material is appropriate, on the one hand, it is ensured that SBR and the negative electrode active material have sufficient contact area, so that SBR can provide sufficient adhesion for the negative electrode active material, so that the negative electrode sheet can maintain good structural stability, and on the other hand, SBR will not completely fill the surface of the negative electrode active material, thereby retaining sufficient active sites on the surface of the negative electrode active material, which is conducive to electrolyte infiltration, increasing the SEI film coverage area on the surface of the negative electrode active material, thereby improving the lithium ion transmission efficiency, and optimizing the lithium ion transmission kinetic characteristics of the negative electrode sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a battery containing the negative electrode sheet. Background Art

[0002] Lithium-ion batteries have many advantages such as high energy density, no memory effect, and low discharge rate. They are widely used in many fields such as portable electronic devices, electric vehicles, and energy storage power stations.

[0003] In lithium-ion batteries, binders are an important factor affecting the stability of electrode structures. The negative electrode binder mainly plays the role of bonding the negative electrode active materials, conductive agents and dispersants to the current collector. Today, the negative electrode binders used by most lithium battery manufacturers are still SBR (polystyrene butadiene copolymer) or its modified products. SBR has good bonding properties. Using SBR as a negative electrode binder can reduce the phenomenon of electrode film stripping and decarbonization during the coating, cutting, stripping and winding of the electrode production, optimize the processing performance of the electrode, and the electrode obtained has good flexibility. However, due to the poor affinity of SBR binder with the electrolyte, it is easy to cause difficulty in the conduction of lithium ions in the binder during charging and discharging, and the internal resistance of the battery increases. This phenomenon is more obvious at low temperatures, which is reflected in the more serious lithium plating of the negative electrode at low temperatures and the poor kinetic performance of the battery. Summary of the invention

[0004] In order to improve the lithium ion transmission efficiency of a negative electrode sheet containing SBR, especially the lithium ion transmission efficiency under low temperature conditions, the present invention provides a negative electrode sheet and a battery containing the same.

[0005] According to a first aspect of the present invention, a negative electrode sheet is provided, which includes a negative electrode active coating, the negative electrode active coating includes a negative electrode active material and a negative electrode binder, and the negative electrode binder includes SBR; the particle size D50 of the negative electrode active material is D1, the particle size D50 of the SBR is D2, D1 and D2 satisfy 6≤D1 / D2≤100.

[0006] In the process of preparing negative electrode sheets using SBR as a negative electrode binder, a negative electrode active slurry containing SBR is generally pre-prepared, the negative electrode active slurry is coated on the surface of the negative electrode current collector, and the negative electrode active slurry is dried to form a negative electrode active coating on the surface of the negative electrode current collector. However, due to the low density of SBR, in the process of the negative electrode active slurry containing SBR not being completely cured, the SBR in the negative electrode active slurry will partially float up to the surface of the coating. After the coating is cured and formed, the SBR located on the surface of the negative electrode active coating will cover a part of the active sites on the surface of the negative electrode active material, resulting in an increase in the electronic impedance and ionic impedance of the negative electrode sheet, affecting the transmission of lithium ions between the positive and negative electrode sheets, and further affecting the kinetic performance of the lithium-ion battery. The present invention relates the particle size D2 of SBR in the negative electrode sheet to the particle size D1 of the negative electrode active material. When the negative electrode active coating of the negative electrode sheet satisfies 6≤D1 / D2≤100, the relative sizes of SBR and the negative electrode active material are appropriate. On the one hand, it is ensured that SBR and the negative electrode active material have sufficient contact area, so that SBR can provide sufficient adhesion for the negative electrode active material, so that the negative electrode sheet can maintain good structural stability. On the other hand, SBR does not completely fill the surface of the negative electrode active material, thereby retaining sufficient active sites on the surface of the negative electrode active material, which is beneficial to the infiltration of the electrolyte, and the SEI film coverage area on the surface of the negative electrode active material is increased, thereby improving the lithium ion transmission efficiency and optimizing the lithium ion transmission kinetic characteristics of the negative electrode sheet.

[0007] According to a second aspect of the present invention, a battery is provided, the battery comprising the above-mentioned negative electrode sheet.

[0008] The negative electrode sheet provided by the present invention is applied to a battery, so that the battery can have good lithium ion transmission kinetics characteristics, especially lithium ion transmission kinetics characteristics under low temperature conditions. DETAILED DESCRIPTION

[0009] In order to improve the problem of ionic impedance and increased ionic impedance of the negative electrode sheet caused by SBR floating up and occupying a large amount of active sites of the negative electrode active material during the coating and drying process of the negative electrode slurry containing SBR, and to improve the kinetic performance of the battery, the present invention provides a negative electrode sheet and a battery containing the same.

[0010] According to a first aspect of the present invention, a negative electrode sheet is provided, which includes a negative electrode active coating, the negative electrode active coating includes a negative electrode active material and a negative electrode binder, and the negative electrode binder includes SBR; the particle size D50 of the negative electrode active material is D1, the particle size D50 of the SBR is D2, D1 and D2 satisfy 6≤D1 / D2≤100.

[0011] In the process of preparing negative electrode sheets using SBR as a negative electrode binder, a negative electrode active slurry containing SBR is generally pre-prepared, the negative electrode active slurry is coated on the surface of the negative electrode current collector, and the negative electrode active slurry is dried to form a negative electrode active coating on the surface of the negative electrode current collector. However, due to the low density of SBR, in the process of the negative electrode active slurry containing SBR not being completely cured, the SBR in the negative electrode active slurry will partially float up to the surface of the coating. After the coating is cured and formed, the SBR located on the surface of the negative electrode active coating will cover a part of the active sites on the surface of the negative electrode active material, resulting in an increase in the electronic impedance and ionic impedance of the negative electrode sheet, affecting the transmission of lithium ions between the positive and negative electrode sheets, and further affecting the kinetic performance of the lithium-ion battery. The present invention relates the particle size D2 of SBR in the negative electrode sheet to the particle size D1 of the negative electrode active material. When the negative electrode active coating of the negative electrode sheet satisfies 6≤D1 / D2≤100, the relative sizes of SBR and the negative electrode active material are appropriate. On the one hand, it is ensured that SBR and the negative electrode active material have sufficient contact area, so that SBR can provide sufficient adhesion for the negative electrode active material, so that the negative electrode sheet can maintain good structural stability. On the other hand, SBR does not completely fill the surface of the negative electrode active material, thereby retaining sufficient active sites on the surface of the negative electrode active material, which is beneficial to the infiltration of the electrolyte, and the SEI film coverage area on the surface of the negative electrode active material is increased, thereby improving the lithium ion transmission efficiency and optimizing the lithium ion transmission kinetic characteristics of the negative electrode sheet.

[0012] Preferably, 6.3≤D1 / D2≤90.9.

[0013] Preferably, D2 = 200-500 nm. SBR with a particle size within the above range still has good bonding properties, so that the negative electrode active materials can be firmly bonded to each other and the negative electrode current collector. At the same time, the volume corresponding to the SBR within this particle size range will not be too low, so that the SBR is easy to encounter obstacles that prevent it from directly floating to the surface of the negative electrode active coating during its movement in the negative electrode slurry, thereby avoiding the accumulation of SBR on the surface of the negative electrode active coating and hindering the interface transmission of lithium ions between the negative electrode active material and the electrolyte.

[0014] Preferably, D2=220-480nm.

[0015] Preferably, D1=3-20 μm.

[0016] The particle size D1 of the negative electrode active material in the negative electrode sheet provided by the present invention and the particle size D2 of the SBR further satisfy D1=3-20 μm while satisfying 6≤D1 / D2≤100, so that a suitable contact area can be maintained between the SBR and the negative electrode active material, ensuring that a certain active site can be exposed on the surface of the negative electrode active material. The negative electrode sheet is applied to the battery, which is conducive to the growth of SEI film near the negative electrode sheet in the later stage of the battery, and can reduce the electronic impedance and ionic impedance of the negative electrode sheet to a certain extent, ensuring the transmission rate of lithium ions between the positive and negative electrode sheets, and giving the battery good kinetic performance.

[0017] Preferably, in the negative electrode active coating, the mass of the negative electrode active material: the mass of SBR = 31.7 to 97.2.

[0018] Preferably, the negative electrode active material includes at least one of a carbon-based negative electrode active material, a silicon-based negative electrode active material, a tin-based negative electrode active material, and a silicon-carbon negative electrode active material.

[0019] Preferably, the negative electrode sheet further includes a conductive agent and a thickener, and the mass ratio is negative electrode active material: conductive agent: thickener = 96-97: 0.3-1.0: 0.5-1.5.

[0020] Preferably, the preparation of the negative electrode sheet comprises the following steps: uniformly mixing the negative electrode active material, the conductive agent, the thickener and the solvent to prepare a negative electrode slurry with a viscosity of 4500 to 5500 mPa·s, then adding a negative electrode binder to the negative electrode slurry, stirring evenly and coating it on both surfaces of the negative electrode current collector to prepare a negative electrode sheet.

[0021] According to a second aspect of the present invention, a battery is provided, the battery comprising the above-mentioned negative electrode sheet.

[0022] The negative electrode sheet provided by the present invention is applied to a battery, so that the battery can have good lithium ion transmission kinetics characteristics, especially lithium ion transmission kinetics characteristics under low temperature conditions.

[0023] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A battery, the preparation method of which comprises the following steps:

[0026] 1. Preparation of negative electrode

[0027] Graphite with a particle size of D50 = 3 μm was mixed with a conductive agent SP and a thickener CMC, and deionized water was added to adjust the slurry viscosity to 5000 mPa·s. Subsequently, SBR with a particle size of D50 = 200 nm was added and stirred evenly to obtain a negative electrode slurry; wherein, calculated by mass ratio, graphite: SBR: conductive agent SP: thickener CMC = 96.59: 1.61: 0.6: 1.

[0028] The negative electrode slurry was evenly coated on the two surfaces of the negative electrode current collector copper foil, and then dried, rolled and sliced ​​to obtain a surface density of 166 g / cm 3 , compacted density is 1.65g / cm 3 The negative electrode.

[0029] 2. Preparation of positive electrode

[0030] The raw materials used to prepare the positive electrode sheet include NCM five-series positive electrode material, conductive agent SP, and binder PVDF. According to the mass ratio, NCM five-series positive electrode material: conductive agent SP: binder PVDF = 97.6:1.2:1.2 are mixed. Among them, the chemical formula of NCM five-series positive electrode material is LiNi 0.5 Co x Mn 0.5-x O2 (0<x<0.5); after the above materials are mixed, a solvent N-methylpyrrolidone (NMP) is added to adjust the solid content of the slurry to about 50% to obtain a positive electrode slurry.

[0031] The positive electrode slurry was evenly coated on the two surfaces of the positive electrode current collector aluminum foil, and then dried, rolled and sliced ​​to obtain a surface density of 272 g / cm 3 , compacted density is 3.5g / cm 3 The positive electrode.

[0032] 3. Preparation of Electrolyte

[0033] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0034] 4. Preparation of Isolation Membrane

[0035] A polyethylene film was selected as the separator.

[0036] 5. Battery Assembly

[0037] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, with the isolation film placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and the battery of this embodiment is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0038] Example 2

[0039] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 500nm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0040] Example 3

[0041] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in the structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 500nm, and the particle size D50 of the graphite is 20μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0042] Example 4

[0043] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the graphite used is 20 μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0044] Example 5

[0045] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is: in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 400nm, the particle size D50 of the graphite is 12μm; the mass ratio of graphite to SBR is 95.2:3.0. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0046] Example 6

[0047] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is: in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 400nm, the particle size D50 of the graphite is 12μm; the mass ratio of graphite to SBR is 97.2:1.0. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0048] Example 7

[0049] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in the structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 400nm, and the particle size D50 of the graphite is 12μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0050] Example 8

[0051] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 400nm, the particle size D50 of the graphite is 12μm; the mass ratio of graphite to SBR is 97.23:0.97. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0052] Example 9

[0053] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in the structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 550nm, and the particle size D50 of the graphite is 3.4μm. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0054] Example 10

[0055] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 480nm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0056] Embodiment 11

[0057] This embodiment prepares a battery with reference to the embodiment 1. Compared with the embodiment 1, the difference in the structure is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 220nm, and the particle size D50 of the graphite is 20μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0058] Comparative Example 1

[0059] This comparative example prepares a battery with reference to Example 1. Compared with Example 1, the difference in composition is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 100 nm, and the particle size D50 of the graphite is 12 μm. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0060] Comparative Example 2

[0061] This comparative example prepares a battery with reference to Example 1. Compared with Example 1, the difference in composition is that in the preparation process of the negative electrode sheet, the particle size D50 of the SBR used is 400nm, and the particle size D50 of the graphite is 2μm. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0062] Test Case

[0063] 1. Participants

[0064] This test example uses the negative electrode sheets and batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 2 as test objects, and tests the adhesion between the coating formed by the negative electrode slurry of the negative electrode sheet and the negative electrode collector, as well as the dynamic performance of the battery at -10°C and 25°C.

[0065] 2. Test content

[0066] (1) Adhesion between the coating of the negative electrode sheet and the negative electrode current collector

[0067] The adhesion between the coating of the negative electrode sheet and the negative electrode collector is tested according to the following steps: A. Cut the battery electrode to be tested into pieces wider than the transparent tape; B. Attach the transparent tape to the side of the electrode sheet containing the coating layer and pre-peel off the head; C. Fix the electrode sheet containing the transparent tape on the steel plate; D. Then use a tensile tester to directly peel off the coating layer, and judge the adhesion strength between the material and the negative electrode collector (foil) based on the size of the tensile force.

[0068] (2) Battery dynamics performance

[0069] The batteries provided in Examples 1 to 11 and Comparative Examples 1 to 2 were charged and discharged for 3 cycles at 1C and 25°C, the battery state of charge SOC was adjusted to 50%, and then discharged at 1C for 10s, and the DC resistance (DCR) under this charge was measured. The calculation formula of DCR at 25°C is (U 末 -U 初 ) / I, where, U 末 is the voltage after discharge, U 初 is the voltage before discharge, and I is the discharge current.

[0070] The batteries provided in Examples 1 to 11 and Comparative Examples 1 to 2 were charged and discharged for 3 cycles at 1C and 25°C, and the temperature of the test box was adjusted to -10°C. The batteries were left for 6 hours, and the battery state of charge SOC was adjusted to 50%. Then, the battery was discharged at 0.3C for 10s, and the DC resistance (DCR) under this charge was measured. The calculation formula of DCR at -10°C is (U 末 -U 初 ) / I, where, U 末 is the voltage after discharge, U 初 is the voltage before discharge, and I is the discharge current.

[0071] 3. Test results

[0072] Table 1 Performance tests of negative electrode sheets and batteries

[0073]

[0074] Among the test objects, the negative electrode sheets prepared in Examples 1 to 11 meet the characteristic of 6≤D1 / D2≤100, while the negative electrode sheet prepared in Comparative Example 2 belongs to the case of D1 / D2<6, and the negative electrode sheet prepared in Comparative Example 1 belongs to the case of D1 / D2>100. Referring to the test result data shown in Table 1, it can be seen that the test objects of this test example are classified based on whether the negative electrode sheets used meet 6≤D1 / D2≤100, and different types of lithium-ion batteries have obvious differences in the adhesion level and DCR level measured in this test example, among which the difference in the DCR value measured under low temperature conditions is more significant.

[0075] From the test results, it can be seen that among the test objects, the DCR level measured for the lithium-ion battery provided in Comparative Example 1 is significantly higher, and after the test, obvious lithium deposition occurs on the negative electrode sheet of the lithium-ion battery provided in Comparative Example 1. This indicates that during the cyclic charge and discharge process of the lithium-ion battery provided in Comparative Example 1, lithium ions are not transmitted smoothly on its negative electrode, and the lithium ion transmission kinetics of the battery are poor. The density of SBR is relatively low, while the D1 / D2 corresponding to the negative electrode used in the lithium ion battery of Comparative Example 1 is as high as 120. In its negative electrode active coating, the particle size of SBR is relatively small relative to the negative electrode active material. Therefore, in the process of preparing the negative electrode active coating, SBR with relatively small density and relatively small volume will float to the surface of the negative electrode active coating along with the incompletely dried negative electrode slurry, and because the particles of SBR are relatively small, it is easy to slide along the surface of the negative electrode active material and tightly fill the gaps between the negative electrode active materials. However, SBR has poor conductivity and poor affinity with the electrolyte. Excessive SBR covering the surface of the negative electrode active material actually makes the contact area between the negative electrode active material and the electrolyte insufficient, making it difficult to form sufficient lithium ion transmission channels between the negative electrode active material and the electrolyte, and is not conducive to the formation of SEI film on the surface of the negative electrode active material. In general, it causes poor transmission of lithium ions between the negative electrode active material and the electrolyte, which is reflected in the poor lithium ion transmission kinetics of the battery.

[0076] On the other hand, the negative electrode sheet in the lithium ion battery of comparative example 2 has low adhesion. After the test, by disassembling the lithium ion battery of comparative example 2 and observing its negative electrode sheet, it can be seen that its negative electrode sheet has obvious negative electrode active coating broken, powdered, expanded and even cracked compared with before entering the test. In sharp contrast, the negative electrode used in the lithium ion batteries of Examples 1 to 11 did not show obvious deformation, damage and the like after the test, and had significantly better structural stability than comparative example 2. The D1 / D2 corresponding to the negative electrode sheet used in the lithium ion battery provided in comparative example 2 is as low as 5, that is, the SBR contained in its negative electrode active coating has a larger particle size than the negative electrode active material, making it difficult for SBR to enter the gap between the negative electrode active materials, and the excessively large particle size makes the overall specific surface area of ​​SBR small. All of the above lead to the inability of SBR to fully contact with the negative electrode active material, so that it is difficult to fully exert the bonding performance of SBR, and the negative electrode active materials are difficult to be firmly combined through SBR, and powdering, expansion and the like occur, which ultimately leads to poor structural stability of the negative electrode sheet. Moreover, when D1 / D2 is too small, although the shielding effect of SBR on the active sites on the graphite surface will be reduced, the particle size of SBR is larger than that of the negative electrode active material, so its adhesion to graphite is also poor, resulting in more gaps between graphite and SBR, which in turn increases the interface resistance between the two, and the final result is an increase in the DCR value. Both of the above reasons will have an adverse effect on the transmission of lithium ions.

[0077] Compared with the data measured by the test objects of the corresponding comparative example 1 and comparative example 2, the test objects of the corresponding embodiments 1 to 11 show good lithium ion transfer kinetics under the premise of maintaining sufficient negative electrode sheet adhesion, and the measured DCR value is low. After the test, the lithium ion batteries of embodiments 1 to 11 are disassembled, and basically no negative electrode lithium precipitation occurs. The negative electrode sheets of embodiments 1 to 11 meet 6≤D1 / D2≤100. At this time, the relative size of SBR and the negative electrode active material is appropriate. On the one hand, it ensures that SBR has sufficient contact area with the negative electrode active material, so that SBR can provide sufficient adhesion for the negative electrode active material, so that the negative electrode sheet can maintain good structural stability. On the other hand, SBR does not completely fill the surface of the negative electrode active material, thereby retaining sufficient active sites on the surface of the negative electrode active material, which is conducive to electrolyte infiltration, increasing the SEI film coverage area on the surface of the negative electrode active material, and thus improving the lithium ion transfer efficiency and optimizing the lithium ion transfer kinetics of the negative electrode sheet.

[0078] The mass ratio of graphite to SBR used in the preparation process of the negative electrode sheets used in the batteries of Examples 1, 2, 3, 4, 7, 9, 10, and 11 is the same. The negative electrode sheets of Examples 1, 3, 7, 10, and 11 satisfy 6.3≤D1 / D2≤90.9, while Examples 2, 4, and 9 do not satisfy 6.3≤D1 / D2≤90.9. The final test results show that the kinetic performance of the batteries of Examples 1, 3, 7, 10, and 11 is better than that of Examples 2, 4, and 9, and the corresponding DCR values ​​are lower than those of Examples 2, 4, and 9.

[0079] In addition, the mass ratio of graphite and SBR used in the preparation process of the negative electrode sheets used in the batteries of Examples 1, 2, 3, 4, 7, 9, 10, and 11 is the same, and the adhesion between the coating of the negative electrode sheet and the negative electrode collector is inversely proportional to the particle size D2 of SBR. The larger the D2, the smaller the adhesion. The adhesion sizes of the above examples are as follows: Example 9 < Example 2 < Example 3 < Example 10 < Example 7 < Example 11 < Example 1 < Example 4.

[0080] In Examples 1 to 11, except for Example 9, the negative electrodes used in the batteries of other examples not only satisfy the relationship of 6≤D1 / D2≤100, but also further satisfy D2=200~500nm, and the adhesion between the coating and the negative electrode current collector is higher than that of Example 9.

[0081] In the process of preparing negative electrode sheets, Examples 5, 6, 7, and 8 all use graphite and SBR of the same particle size, but the mass ratio of the two is different, namely 31.7, 97.2, 60, and 100, respectively. The corresponding adhesion and DCR are as follows: Example 5> Example 7> Example 6> Example 8. The above results indicate that when the particle sizes of graphite and SBR remain consistent, as the mass ratio of graphite to SBR increases, the adhesion between the coating of the negative electrode sheet and the negative electrode current collector and the DCR both decrease.

[0082] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode active coating, the negative electrode active coating comprises a negative electrode active material and a negative electrode binder, and the negative electrode binder comprises SBR; The particle size D50 of the negative electrode active material is denoted as D1, the particle size D50 of the SBR is denoted as D2, and the D1 and D2 satisfy the following conditions: D2=400-500 nm, and 6.3≤D1 / D2≤40.

2. The negative electrode sheet according to claim 1, characterized in that: D1=3~20μm.

3. The negative electrode sheet according to claim 1, characterized in that: In the negative electrode active coating, the mass of the negative electrode active material: the mass of the SBR = 31.7 to 97.

2.

4. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material includes at least one of a carbon-based negative electrode active material, a silicon-based negative electrode active material, a tin-based negative electrode active material, and a silicon-carbon negative electrode active material.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation of the negative electrode sheet comprises the following steps: The negative electrode active material, conductive agent, thickener and solvent are mixed evenly to prepare a negative electrode slurry with a viscosity of 4500-5500 mPa·s, and then the negative electrode binder is added to the negative electrode slurry, stirred evenly and coated on the two surfaces of the negative electrode collector to prepare the negative electrode sheet.

6. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as claimed in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Secondary battery and method for manufacturing secondary battery

    CN111129430A